2022
DOI: 10.3390/foods11172671
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting and Burnout as Predictors of Food Safety Behaviors in the Foodservice Industry

Abstract: This study aimed to investigate whether job crafting, burnout, and work engagement predict food safety behaviors in the foodservice industry. It was a cross-sectional study conducted in Cuiabá (Brazil) among foodservice workers. Four instruments were used among foodservice workers for the examination: (a) job demands and resources, (b) job satisfaction, (c) burnout, and (d) work engagement. Food safety practices were measured using a validated risk-based checklist. Partial least squares structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Although, Tomasevic et al [ 20 ] did not assess the relationship between food safety culture and conscientiousness or feelings of burnout/job stress, it was mentioned as a study limitation. Nascimento et al [ 56 ] on the other hand indicated that mitigating burnout can be an important strategy to improve food safety behavior in the food service industry in Brazil. The low mean score for burnout/job stress in this study could be related to fear of job loss, salary drop, work overload as well as possible work-unrelated stresses (Covid-19 pandemic and the Lebanese economic crisis).…”
Section: Resultsmentioning
confidence: 99%
“…Although, Tomasevic et al [ 20 ] did not assess the relationship between food safety culture and conscientiousness or feelings of burnout/job stress, it was mentioned as a study limitation. Nascimento et al [ 56 ] on the other hand indicated that mitigating burnout can be an important strategy to improve food safety behavior in the food service industry in Brazil. The low mean score for burnout/job stress in this study could be related to fear of job loss, salary drop, work overload as well as possible work-unrelated stresses (Covid-19 pandemic and the Lebanese economic crisis).…”
Section: Resultsmentioning
confidence: 99%